THE STUDENTS’ INTEREST ON THE USE OF PICTURE SERIES MEDIA IN WRITING - Syayyidina Ali; Emirati (Almeera Education, 2022)
Media has a great role in learning as well as in writing, how to help the students easier in expressing their idea and constructing their writing as well. This study aims at describing the students’ interest on the use of picture series media in writing. The design of this study was a descriptive model which engaged 25 students as sample. It was conducted at Muhammadiyah University of Bulukumba, South-Sulawesi. In collecting data, the researcher used questionnaire in rating scale form; whether (1) strongly agree (2) Agree (3) Undecided (4) Disagree (5) Strongly Disagree with the questions or statements given. It contained ten positive and closed statements about the usage of picture series media in writing which was given after treating the students for several meetings by using that media. The percentage of each answer or response on the questionnaire was calculated. The researcher utilized the formula where the number of frequency is multiplied by 100 percent (%) and then divided by the total number of respondents, and then converting the questionnaire data into percentages. The result of the students’ response indicated that picture series is an interesting media used in writing because of helping them construct their writing, grow their ideas, arrange the chronological order, focus on writing, and etc. It can be concluded that picture series is an interesting media used in writing. The mean percentage score showed that 84.4% of strongly agree, 15.2% of agree, 0.4% of undecided, none of student stated disagree and strongly disagree with the statements on the questionnaire.